(untitled) (Journal of Fiber Bioengineering and Informatics, 2008)
This paper describes the relevance of knowledge of processes that happen at the skin for sports clothing design. It looks at skin temperature distribution while cooling, relevant e.g. to outdoor winter sports and mountaineering, at sweat distribution over the body while running, relevant e.g. to clothing designed for running in general and more particularly for exercise in warm and hot climates, and finally it looks into regional skin sensitivity, relevant for all fields of sports clothing design. As these areas interact heavily, the sports clothing designer needs to be aware of their influences and their interactions in order to optimise the clothing for the specific type of sport at hand.